The association between organizational culture and teachers’ organizational commitment in Bahir Dar Polytechnic College, the State of Amhara - Berhan Kefyalew Taye; Melaku Mengistu Gebremeskel (Bahir Dar Journal of Education)
This study attempted to examine the relationship between the organizational culture and teachers’ organizational commitment in Bahir Dar Polytechnic College–in Ethiopia. It investigated the status of organizational culture, the level of teacher commitment, the relationship between the organizational culture and the organizational commitment of teachers in the college, and the influence of the former variable over the latter. The study employed the correlational design of the quantitative research approach in which 93 teachers were involved to fill in the questionnaire. These participants were recruited through a systematic random sampling technique. Data were analyzed using descriptive (mean, standard deviations, and one sample t-test) as well as inferential statistics (correlation and multiple linear regression). Results indicated that the college has a well-solidified organizational culture. It also revealed that the affective and continuance commitments toward the college kept teachers at the college. In addition, organizational culture as a whole and its four components all alike correlated with every organizational commitment dimension strongly and positively. On the other hand, involvement and adaptability had only moderate positive relationships with normative commitment, and the same applied to the association between mission and continuance commitment. Moreover, three of the four components of organizational culture – mission, consistency, and involvement – significantly predicted the commitment of teachers in the college. Hence, the insights into organizational culture laid down by this study help the college to get the best out of its employees by regularly examining and redesigning its organizational culture to eventually boost all dimensions of teachers’ organizational commitment.